Rules on the Web: From Theory to Applications 8th International Symposium, RuleML 2014, Co-located with the 21st European Conference on Artificial Intelligence, ECAI 2014, Prague, Czech Republic, August 18-20, 2014, Proceedings - Bikakis, Antonis; Fodor, Paul.; Roman, Dumitru; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 8th International RuleML Symposium, RuleML 2014, co-located with the 21st European Conference on Artificial Intelligence, ECAI 2014, held in Prague, Czech Republic, in August 2014. The 17 full and 6 short papers presented together with 3 keynote talks were carefully reviewed and selected from 48 submissions. The papers cover the following topics: semantic web rule languages and standards, rule engines, formal and operational semantics and rule-based systems, the relation between natural language and rules, automation of business rules generation from existing data, and aspects related to legal rules and norms for web and corporate environments.
Keywords: Artificial intelligence; Application software; Computer logic; Artificial Intelligence; Information Systems Applications (incl. Internet).; Logics and Meanings of Programs; Computer Applications